Konseling Multikultural Bebas Bias di Lingkungan Kampus - Gabriani Paranda; Gita Massora; Dewi Balandatu; Resky Wilfa Balalembang; Ronaldo Stefanus (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Multicultural counseling has become an essential need within increasingly diverse university environments. Students bring various cultural backgrounds, beliefs, languages, and social experiences, which requires counseling services to respond fairly and without bias. This papper explores efforts to build bias-free multicultural counseling through three main areas: a theoretical understanding of cultural competence, practical strategies for reducing counselor bias, and an implementation model that higher education institutions can apply. The approach highlights the importance of counselor self-awareness, the ability to recognize cultural dynamics, and the use of counseling techniques that are sensitive to diversity. In addition, the papper discusses the role of campus policies and ongoing training in creating inclusive services. By integrating theory and practice, campus counseling is expected to provide a safe space for all students. A bias-free approach not only strengthens counseling effectiveness but also contributes to an academic climate that respects differences. This papper offers recommendations to help universities develop counseling systems that can respond to an increasingly plural society.